Novo modelo de gestão organizacional para as empresas brasileiras de telecomunicações: o caso da Telerj Celular - Castro, Ana Lúcia Teixeira de (2000)
The dissertation's aim is to present the new management model to the brazilian telecommunication enterprises, established in 1997, taking the particular case of Telerj Celular. For this, we analyse internal factors that influenced the change of the management model, as well as the State's hole in relation to the brazilian telecommunication politics, based on its employees' point of view.